SEXIST VERBAL VIOLENCE ON SOCIAL MEDIA: A PSYCHOLINGUISTIC STUDY OF ABUSIVE LANGUAGE - Rahmawati Rahmawati; Herman Herman; Sutarno Sutarno; Arwin Tannuary; Nurainun Hasibuan; Nguyen Van Thao (English Review: Journal of English Education, 2025)
This study investigates the phenomenon of sexist verbal violence on social media through a psycholinguistic lens, focusing on the linguistic forms, communicative functions, and psychological impacts of abusive language directed at women. Triggered by the growing prevalence of gendered hate speech on platforms such as TikTok and Instagram, particularly targeting female public figures, this research employs a descriptive qualitative method supported by speech act theory (Austin, 1962; Searle, 1969). A total of 150 comments were analyzed, of which 55 were identified as containing sexist verbal abuse. The findings reveal that these utterances typically involve illocutionary speech acts such as insults, verbal sexual harassment, gender stereotyping, and moral policing. The corresponding perlocutionary effects include emotional harm, such as shame, fear, and diminished self-confidence in the victims. From a psycholinguistic perspective, the production of such language reflects internalized gender bias, affective disinhibition, and the activation of negative cognitive schemas. The study further highlights how digital anonymity and ethical disinhibition enable users to express aggression with minimal accountability. Overall, the results indicate that language is strategically used to exert power and reinforce patriarchal norms within digital discourse. This research underscores the need for greater linguistic awareness, the promotion of digital empathy, and the implementation of more responsive communication ethics in online environments. Creating safer, more inclusive digital spaces requires a multidimensional approach involving education, platform regulation, and cultural change in how language is used and interpreted.